2022
DOI: 10.3168/jds.2021-20638
|View full text |Cite
|
Sign up to set email alerts
|

A survey of calf management practices and farmer perceptions of calf housing in UK dairy herds

Abstract: Adoption of optimal management techniques for rearing dairy calves has significant effects on their health, welfare, and productivity. Despite much published literature on best practice, calf morbidity and mortality rates remain high. This survey aimed to establish current calf management practices in the United Kingdom, along with farmer perceptions surrounding different housing types. A survey containing 48 questions was distributed online to UK farmers via social media, online forums, and a convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Similarly, accelerometers were reported to be a commonly researched PDT on dairy farms (Slob et al, 2020). Additionally, less than half of producers in the UK use individual housing, demonstrating a need for methods that detect diseases in socially housed calves (Mahendran et al, 2021). Thus, investigating the potential of familiar PDT such as an automated feeder and an accelerometer to indicate a calf that has outward signs of respiratory disease and is positive for lung consolidation is valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, accelerometers were reported to be a commonly researched PDT on dairy farms (Slob et al, 2020). Additionally, less than half of producers in the UK use individual housing, demonstrating a need for methods that detect diseases in socially housed calves (Mahendran et al, 2021). Thus, investigating the potential of familiar PDT such as an automated feeder and an accelerometer to indicate a calf that has outward signs of respiratory disease and is positive for lung consolidation is valuable.…”
Section: Introductionmentioning
confidence: 99%
“…The milk fed to calves can be either milk replacer, whole milk from the bulk tank, milk from recently calved cows or milk of lower quality (e.g. waste milk from cows with mastitis (Hayer et al., 2021 ) or from cows treated with antimicrobials (Mahendran et al., 2022 )), although this is not good agricultural practice. According to recent surveys, in 72.4% of farms in western Germany calves were fed waste milk (Hayer et al., 2021 ), and in 3.7% of farms in UK calves were provided with waste milk containing antimicrobials (Mahendran et al., 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…In Chilean farms, it could be suggested to employ calf-specific personnel that may lead to increasing the specialisations of skills in the staff and the ability of veterinary practices to target training courses. In the United Kingdom (Mahendran et al, 2022) the development and implementation of standard operating procedures in conjunction with veterinary practices is becoming more common and even a requirement for some dairy contracts and this could be applied in Chile in the near future.…”
Section: Calf Raising Husbandry Practicesmentioning
confidence: 99%
“…In this study, the criterion for weaning partly agrees with studies from Europe. In the United Kingdom, farmers use age as the main weaning criteria, with an age ranging from 6 to 12 weeks (Mahendran et al, 2022). In Czech dairy herds, Stanek et al (2014) reported that calving in group pens predominated (67% of farms) and the main weaning criterion was age (61.7%) followed by intake of starter and concentrated feeds.…”
Section: Calf Raising Husbandry Practicesmentioning
confidence: 99%